HUBUNGAN PENERIMAAN RESPECTFUL MATERNITY CARE (RMC) DENGAN KEPUASAN IBU BERSALIN DI PUSKESMAS BANGETAYU KECAMATAN GENUK KOTA SEMARANG - Sherly Icha Puspita; Surani, Endang (STIKES Yarsi Mataram, 2025)
Background: Respectful Maternity Care (RMC) is a maternal health care approach that emphasizes the respect for women's human rights, including the right to dignified treatment, privacy, and freedom from violence and discrimination during childbirth. A lack of respectful care during labor can negatively impact maternal satisfaction and reduce the likelihood of returning to health facilities for future deliveries. Objective: This study aims to determine the relationship between the acceptance of Respectful Maternity Care (RMC) and maternal satisfaction among postpartum women at Bangetayu Public Health Center, Genuk Subdistrict, Semarang City. Methods: This was a quantitative study using a cross-sectional approach. The sampling technique applied was total sampling, with 45 postpartum mothers as respondents. The instruments used were the QRMCQI questionnaire to measure RMC acceptance and the BSS-R to assess maternal satisfaction. Data were analyzed using the Spearman Rank test. Results: The majority of respondents were within the ideal reproductive age (20–35 years), had a secondary or higher education level, were housewives, and were multiparous. A total of 77.8% of mothers had a high level of RMC acceptance, and 62.2% reported good satisfaction with delivery services. Statistical analysis revealed a significant relationship between RMC acceptance and maternal satisfaction, with a p-value of 0.004 (p < 0.05). Conclusion: There is a significant relationship between the acceptance of Respectful Maternity Care and maternal satisfaction at Bangetayu Public Health Center. Enhancing the implementation of RMC principles can contribute to improving patient satisfaction with maternity services.